171k views
0 votes
Subtract –3(4x – 1) from 4(5x + 7).

User Jabed
by
5.5k points

1 Answer

4 votes

ANSWER





4(5x+7)--3(4x-1)=32x+25






Step-by-step explanation

Note that the expression which comes immediately after from comes first.



4(5x+7)--3(4x-1)



We convert the minus minus to plus




4(5x+7)--3(4x-1)=4(5x+7)+3(4x-1)




We expand to obtain,



4(5x+7)--3(4x-1)=20x+28+12x-3)



We group like terms to obtain,



4(5x+7)--3(4x-1)=20x+12x+28-3



We simplify to obtain,




4(5x+7)--3(4x-1)=32x+25



User Jonathan Callen
by
4.7k points